Appliance Diffusion Model for Energy Efficiency Standards and Labeling Evaluation in the Capital of Lao Pdr - Hajime Sasaki; Ichiro Sakata; Weerin Wangjiraniran; Sengprasong Phrakonkham (Journal of Sustainable Development of Energy, Water and Environment Systems, 2015)

(untitled)
Because of the rapid growth of energy demand in developing countries, policies for energy efficiency are receiving increasing attention. Although energy efficiency standards and labeling (EES&L) is a standard policy tool in many countries, some developing countries, such as Lao PDR, have not yet implemented them fully. In order to understand the potential impact of EES&L, this paper aims at collecting data that contribute to EES&L and at analysing appliance possessions in Vientiane City, Lao PDR. We conducted an interview survey on 600 households in Vientiane City and performed logistic regression analysis that set possession of appliances as the dependent variable. As a result of the analysis, we identified that the income level and the electricity consumption are the principal independent variables and the relationship of these variables with possession rates depends on appliances. Our model helps identify appliances that are expected to be in high demand associated with either economic growth or human population increase in Vientiane City.